Force outputs during squats performed using a rotational inertia device under stable versus unstable conditions with different loads - Vazquez-Guerrero, J.; Moras, G.; Baeza, J.; Rodriguez-Jimenez, S. (PLOS ONE, 2016)
The purpose of the study was to compare the force outputs achieved during a squat exercise using a rotational inertia device in stable versus unstable conditions with different loads and in concentric and eccentric phases. Thirteen male athletes (mean ± SD: age 23.7 ± 3.0 years, height 1.80 ± 0.08 m, body mass 77.4 ± 7.9 kg) were assessed while squatting, performing one set of three repetitions with four different loads under stable and unstable conditions at maximum concentric effort. Overall, there were no significant differences between the stable and unstable conditions at each of the loads for any of the dependent variables. Mean force showed significant differences between some of the loads in stable and unstable conditions (P < 0.010) and peak force output differed between all loads for each condition (P < 0.045). Mean force outputs were greater in the concentric than in the eccentric phase under both conditions and with all loads (P < 0.001). There were no significant differences in peak force between concentric and eccentric phases at any load in either stable or unstable conditions. In conclusion, squatting with a rotational inertia device allowed the generation of similar force outputs under stable and unstable conditions at each of the four loads. The study also provides empirical evidence of the different force outputs achieved by adjusting load conditions on the rotational inertia device when performing squats, especially in the case of peak force. Concentric force outputs were significantly higher than eccentric outputs, except for peak force under both conditions. These findings support the use of the rotational inertia device to train the squatting exercise under unstable conditions for strength and conditioning trainers. The device could also be included in injury prevention programs for muscle lesions and ankle and knee joint injuries.